Endoscopic Follow-Up of Positive Fecal Occult Blood Testing in the Ontario FOBT Project. (2007) - Paszat, Lawrence; Rabeneck, Linda; Kiefer, Lori; Mai, Verna; Ritvo, Paul; Sullivan, Terry
Abstract : BACKGROUND: The Ontario FOBT Project is a pilot study of fecal occult blood testing (FOBT) for colorectal cancer screening conducted among age-eligible volunteers (50 to 75 years) in 12 of 37 public health regions in Ontario. METHODS: Volunteers responded to invitations from primary care practitioners (PCPs) in six regions, and from public health programs in the remaining regions. FOBT collection kits were distributed from routine laboratory specimen collection sites, to which completed kits were returned. Results were sent to PCPs in all 12 regions, with copies sent to the study office at Cancer Care Ontario (Toronto, Ontario). Follow-up of positive results was at the discretion of the PCPs. The study files contained the unique Ontario Health Insurance Numbers, the date of the analyses, the number of satisfactory slides and the results for each slide. The Ontario Health Insurance Numbers were encrypted for each participant, and along with the study file, were linked to medical billing claims, hospital records and aggregate demographic data. RESULTS: Among participants with positive results (men 3.5% and women 2.2%), the median time from date of FOBT analysis to date of colonoscopy was 121 days among men and 202 days among women. At the end of follow-up, after positive FOBT (six to 17 months), 73% of men and 56% of women had proceeded to colonoscopy. CONCLUSION: Although colonoscopy appeared to be acceptable to the majority of participants with positive FOBT, accessibility problems was the likely explanation for lengthy intervals between the date of positive FOBT and its performance. Differences between the experiences of men and women require further investigation.